Ethnic differences in pre-admission levels of physical activity in patients admitted with myocardial infarction. - Lip, G; Cader, M; Lee, F; Munir, S; Beevers, D (1996)
BACKGROUND: Regular exercise is generally considered to reduce the risk of coronary heart disease. Reduced levels of physical activity in Indo-Asians may partly explain why patients from this ethnic group sustain so many heart attacks. AIM: To investigate ethnic differences in pre-admission levels of physical activity amongst patients admitted with myocardial infarction and triggers for the acute cardiac event. DESIGN: Cross-sectional study using standard Baecke questionnaire, which provided a semi-quantitative work score, sport score, leisure score and total activity score of general daily activities, with additional questions on activity at the onset of chest pain. SETTING: Coronary Care Unit, City Centre Teaching Hospital. PATIENTS AND RESULTS: We studied 100 consecutive patients (76 males, mean age 62.3 years, S.D. 12.5; 74 caucasians, 26 Indo-Asians) admitted with myocardial infarction. Most patients were engaged in sedentary activities, including lying in bed (25%), sitting (19%), watching television (14%) and sleeping (6%), whilst only 21% of patients were engaged in physical activity at chest pain onset; there were, however, no ethnic differences in activity at chest pain onset. There was a diurnal variation in chest pain onset, with the mode between 08:00 and 10:00 h. As the mean age of Indo-Asians was significantly lower than caucasians in the whole group (56.3 vs. 64.4 years; t-test, P < 0.002), the Baecke questionnaire analysis was confined to only male patients aged < 70 years (n = 56). Indo-Asian patients with myocardial infarction were found to have a significantly lower overall physical activity score (3.78 vs. 5.33; P = 0.003), leisure time physical activity (2.43 vs. 2.74; P < 0.05) and sporting score (0.14 vs. 0.82; P < 0.01) when compared to caucasians, despite a similar mean age and body mass index. CONCLUSION: The majority of myocardial infarction patients were engaged in sedentary activities at chest pain onset. Although there were no differences between caucasians and Indo-Asians in activity at symptom onset, Indo-Asian patients had a significantly lower overall physical activity score, leisure time physical activity and sporting score compared to caucasians. The lower general physical activity amongst Indo-Asians may in part contribute to the high prevalence of ischaemic heart disease amongst this ethnic group.